Integrative STEM-R Pedagogy and Students’ Critical Thinking: A Study in Physics Learning at Madrasah Aliyah - Muhammad Abror Muzakkir Muda; Sri Purwaningsih; Nazarudin; Musli (Didaktika: Jurnal Kependidikan, 2026)
Developing students’ critical thinking skills remains a central challenge in contemporary science education, especially in physics learning that demands analytical reasoning and reflective understanding. Integrative pedagogical models such as the STEM-R (Science, Technology, Engineering, Mathematics, and Religious Values) approach have emerged to promote deeper engagement by connecting scientific inquiry with moral reflection. This research aimed to analyze the influence of STEM-R-based Problem-Based Learning (PBL) on students’ critical thinking skills compared with conventional PBL. A quasi-experimental design with a nonequivalent control group was employed, involving 46 students from MAN 2 Kota Jambi, consisting of 24 in the experimental class and 22 in the control class. The experimental group received PBL integrated with STEM-R, while the control group was taught using standard PBL without reflective or integrative elements. Data were collected through validated critical thinking assessments and analyzed using the Shapiro–Wilk test, Wilcoxon Signed Rank Test, and Mann–Whitney U Test. The findings indicated significant improvement in both groups, with a higher increase in the experimental class (Z = 4.108, p < 0.001) than in the control class (Z = 2.944, p = 0.003). The between-group comparison showed no significant difference (p = 0.288), although the experimental class achieved a higher mean trend. These results suggest that embedding reflective and scientific integration through STEM-R can enhance students’ analytical and evaluative reasoning in physics learning.